Android-Based Mobile Learning in Genetics Subject - Megahati S, Ruth Rize Paas; Azhar; Febri Yanti (RADINKA JAYA UTAMA PUBLISHER, 2022)
The use of ICT-based learning media can make learning more effective. One of the ICT-based learning media that can be used as a learning medium that is operated on a smartphone device is mobile learning (m-learning). The research aims to review related research to produce new findings. M-learning is developed in a multimedia format that provides text, images, audio, and video. The ease of internet access through cellular phone devices such as Blackberries, iPhones, PDAs, and smartphones makes it easier to make learning applications using an Android-based system. The results of developing learning media based on Android mobile smartphones show that students’ motivation and learning outcomes increase. Learning media based on an Android mobile smartphone is produced as a supplement to the genetics course. Learning media based on an Android mobile smartphone has a positive impact and a breakthrough from ICT advances to improve the quality of learning.